Pemijahan Semi Buatan dengan Teknik Striping Pada Ikan Lele (Clarias gariepinus) - Nada, Qothrun; Rahmadani, Thoy Batun Citra (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Freshwater fish, catfish (Clarias gariepinus) is one type of fish for consumption that has high demand. However, catfish production has decreased over the past three years due to constraints in the provision of seeds, especially due to seasonal spawning. This study aims to overcome these constraints through artificial spawning techniques with ovaprim hormone injection and stripping methods. The activity was carried out at the Lingsar Fish Seed Center (BBI), West Lombok in July–August 2024. The process includes pond preparation, broodstock selection, hormone injection, stripping, egg hatching, nursery, and larval maintenance. The results showed that the number of eggs obtained was 61,128, with a hatching rate of 79.99% and a larval survival rate of 72.94%. These results indicate that the artificial spawning method with ovaprim hormone is effective in increasing catfish seed production, and is able to produce seeds in optimal quantity and quality.